Tailored Charge Transfer Kinetics in Precursors for Organic Radical Batteries: A Joint Synthetic‐Theoretical Approach. Issue 2 (30th November 2022) - Zens, Clara; Friebe, Christian; Schubert, Ulrich S.; Richter, Martin; Kupfer, Stephan
Abstract: The development of sustainable energy storage devices is crucial for the transformation of our energy management. In this scope, organic batteries attracted considerable attention. To overcome the shortcomings of typically applied materials from the classes of redox‐active conjugated polymers (i. e., unstable cell voltages) and soft matter‐embedded stable organic radicals (i. e., low conductivity), a novel design concept was introduced, integrating such stable radicals within a conductive polymer backbone. In the present theory‐driven design approach, redox‐active (2, 2, 6, 6‐tetramethylpiperidin‐1‐yl)oxyls (TEMPOs) were incorporated in thiophene‐based polymer model systems, while structure‐property relationships governing the thermodynamic properties as well as the charge transfer kinetics underlying the charging and discharging processes were investigated in a systematical approach. Thereby, the impact of the substitution pattern, the length as well as the nature of the chemical linker, and the ratio of TEMPO and thiophene units was studied using state‐of‐the‐art quantum chemical and quantum dynamical simulations for a set of six molecular model systems. Finally, two promising candidates were synthesized and electrochemically characterized, paving the way to applications in the frame of novel organic radical batteries. Abstract : Radical approach : Molecular models of stable organic radicals incorporated in a conjugated backbone, with application in the field of organic radical batteries, are investigated by means of multiconfigurational methods. The theory‐guided design allows to tune the charge transfer kinetics as well as the underlying thermodynamics. Auspicious systems are synthesized and characterized electrochemically.